A Case of Previously Undiagnosed Systemic Lupus Erythematosus and Mycobacterium tuberculosis Infection Presenting as Diffuse Alveolar Hemorrhage - Henna Iqbal; Benny Screws; Muhammad S. Khan (Case Reports in Rheumatology)
Diffuse alveolar hemorrhage (DAH) is described as the collection of blood in alveolar spaces caused by damaged pulmonary vasculature. It often presents as a life-threatening medical emergency that requires urgent medical intervention along with timely diagnosis and management of the underlying cause. We hereby report a 19-year-old female who presented with clinical and radiological characteristics consistent with DAH. Laboratory workup studies revealed a diagnosis of systemic lupus erythematosus (SLE) as well as Mycobacterium tuberculosis (MTB) infection. This report describes an extremely unusual case of undiagnosed SLE and coexistent tuberculosis presenting as DAH. This leads to an interesting possibility of risks in patients with immune-mediated vasculitis towards developing severe pulmonary disease in the setting of pulmonary mycobacterial infection.